The association of metabolic profile of folate with diabetic kidney disease: evidence from 2011–2020 cycles of the NHANES - Yali Liang; Lei Ding; Mengjun Tao; Yu Zhu (Renal Failure)
Aims Diabetic kidney disease (DKD) develops in approximately 40% of patients with type 2 diabetes mellitus (T2DM). The role of folate metabolites in the progression from T2DM to DKD has not been clearly articulated. Our aim was to assess the association of folate metabolites with DKD.Methods We conducted a cross-sectional study sourced from the U.S. National Health and Nutrition Examination Survey from 2011 to 2020. Several forms of folate were measured. DKD was defined as diabetes with albuminuria or impaired glomerular filtration rate. Odds ratios (ORs) and 95% confidence intervals (CIs) were estimated by logistic regression.Results Of the 3,461 diabetes patients, 1,349 (38.98%) were diagnosed with DKD. Serum total folate and 5-Methyl-THF were negatively associated with DKD, the OR for comparing extreme quintile were both 0.73 (0.57–0.94). However, a positive association of RBC folate, UMFA, Non-5-Methyl-THF, and MeFox with DKD was observed with extreme quintile OR of 1.41 (1.10–1.82), 1.60 (1.24–2.07), 1.53 (1.20–1.96), and 3.45 (2.65–4.50). Furthermore, the ratio of UMFA to 5-Methyl-THF exhibited a positive association with DKD, with extreme quintile OR of 1.94 (1.50–2.50).Conclusions Our findings suggested that guidelines and interventions highlighting the importance of promoting 5-Methyl-THF and reducing UMFA might have significant benefit for the management of patients with diabetes.